THE ACETIC ACID PRODUCTION BY MODELING OXIDATION OF ETHYLENE WITH ASPEN PLUS - Abir Maiuf; Nizar Ramadan (Surman Journal of Science and Technology, 2024)
This study investigates the design and optimization model of acetic acid production by oxidation of ethylene using Aspen Plus software. The input to simulation process is the vapor feed stream with CO2, N2 as bottom stream and H2O as top input stream. The research aims to understand and study the production process of acetic acid and study the operational variables and their effects on the production. According to simulation model, the acetic acid has been produced as liquid in bottom stream after six stages inside absorber. Moreover, the flow rate, temperature and pressure have been controlled and analyzed as sensitivity parameters. The basic product is acetic acid produced with mole flow about 0.6 kmol/hr and the mole fraction about 0.004 at 30.3 °C temperature and 10 bar pressure.